Community Engagement in Social Innovation Research: A Global Sequential Mixed Methods Analysis - Ahumuza, Emmanuel; Moscibrodzki, Patricia; Awor, Phyllis (ResearchSquare, 2022)
Social innovation in health provides innovative solutions to address healthcare delivery gaps and it relies on engaging community. However, little is known about factors that influence community engagement in health research. The study sought an in-depth understanding of elements of community engagement in social innovations identified by the global social innovation in health initiative network.
Keywords: Community Engagement, Social Innovation, Health, Mixed methods